Aboveground biomass allocation in a managed forest of Pinus patula in Zacualtipán, Hidalgo, Mexico - Chávez-Aguilar, Griselda; Ángeles-Pérez, Gregorio; Pérez-Suárez, Marlín; López-López, Miguel Ángel; García-Moya, Edmundo; Wayson, Craig (Instituto de Ecología, A.C., 2016)
Aboveground biomass accumulation and allocation to the structural components of trees is crucial in managed forests, both in terms of timber productivity and the reactivation of different ecosystem processes. In this study, we analyzed the pattern of accumulation of aboveground total biomass and its allocation among stems, branches, bark and foliage in a chronosequence of managed Pinus patula forests in Zacualtipán, Hidalgo. Total aboveground biomass (TAB) and its allocation to structural components were estimated by using allometric equations in stands with different numbers of years since harvest, in different years of measurement (2005, 2008 and 2012). We found that the TAB increased with time since harvest, with highly significant differences (p<0.0001) among stand ages. The stand with 30 years since harvest showed an aboveground biomass (AB) of 178.1 Mg ha-1 which was only 20% lower than that estimated for the stand without harvest (AN), indicating that a managed forest could reach levels of aboveground biomass similar to those of the AN, but in less time. Aboveground biomass allocation was made in the following order: stem> branches> bark> foliage. Allocation favored the stem as a commercial timber product, which is the main objective of these managed forests. The pattern of aboveground biomass allocation among the structural components of the trees reflects the fact that forest management in temperate forests operates as an important alternative for the recovery of degraded forests. Because of climate change, it can also represent an appropriate strategy for carbon sequestration and mitigation of carbon dioxide emissions.